Préparation des perchlorates d’aluminium, de gallium et d’indium anhydres en solution méthanolique - J. Haladjian; P. Bianco (CHIMIA)
The aluminium, gallium, indium anhydrous perchlorates are prepared in methanolic solution by double decomposition of their halides, AlCl3, GaCl3, Inl3, respectively, by silver perchlorate. The reaction is surveyed by potentiometric method with a silver electrode.